2007
DOI: 10.1152/ajpendo.00372.2005
|View full text |Cite
|
Sign up to set email alerts
|

Calcium receptor stimulates chemotaxis and secretion of MCP-1 in GnRH neurons in vitro: potential impact on reduced GnRH neuron population in CaR-null mice

Abstract: The factors controlling the migration of mammalian gonadotropin-releasing hormone (GnRH) neurons from the nasal placode to the hypothalamus are not well understood. We studied whether the extracellular calcium-sensing receptor (CaR) promotes migration/chemotaxis of GnRH neurons. We demonstrated expression of CaR in GnRH neurons in the murine basal forebrain and in two GnRH neuronal cell lines: GT1-7 (hypothalamus derived) and GN11 (olfactory bulb derived). Elevated extracellular Ca2+concentrations promoted che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 56 publications
1
37
0
Order By: Relevance
“…There is evidence to suggest that maternal inflammation dramatically disturbs the cytokine balance in fetuses, producing a long-term programming effect on neuronal development [19,25,26]. In recent years, data have been accumulated on the involvement of cytokines in the development of olfactory structures and migration of GnRH neurons [14,16]. We demonstrated that LPS treatment can significantly increase the levels of maternal serum proinflammatory cytokines within 1.5 h and the effect was still evident at 3 h for IL-6, MCP-1, LIF and TNF-α (fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence to suggest that maternal inflammation dramatically disturbs the cytokine balance in fetuses, producing a long-term programming effect on neuronal development [19,25,26]. In recent years, data have been accumulated on the involvement of cytokines in the development of olfactory structures and migration of GnRH neurons [14,16]. We demonstrated that LPS treatment can significantly increase the levels of maternal serum proinflammatory cytokines within 1.5 h and the effect was still evident at 3 h for IL-6, MCP-1, LIF and TNF-α (fig.…”
Section: Discussionmentioning
confidence: 99%
“…Using GN11 cells as a model of immature, migratory GnRH neurons, Magni et al [16] showed that LIF induced their chemokinesis. MCP-1 and its receptor, chemokine (C-C motif) receptor-2 (CCR2), were found to be expressed in the hypothalamic GnRH neurons as well as in the GT1-7 and GN11 cell lines, with MCP-1 stimulating migration of these immature GnRH neurons [14]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(21). In gonadotropin-releasing hormone neurons the activation of these Ca 2þ receptors promotes cell migration (35).…”
Section: Homo-and Hetereocellular Interactions In Ca 2þ Regulation Ofmentioning
confidence: 99%
“…The soluble Ca 2+ concentration is approximately 1.1-1.3 mM in the extracellular fluids of tissues (Breitweiser, 2008) and 2.5 mM in blood (Bronner, 1997). Evidence suggests that free extracellular Ca 2+ might play a role as a chemoattractant in addition to cell-type-specific chemoattractants in a variety of developmental processes, including embryonic development (Adams et al, 2006;Chattopadhyay et al, 2007;Reitz et al, 1977), wound healing (Menon et al, 1985;Morris and Chan, 2007), angiogenesis (Aguirre et al, 2010), the immune response (Olszak et al, 2000) and tissue maintenance (Quarles et al, 1997). For example, mammalian gonadotropin-releasing hormone (GnRH) neurons undergo chemotaxis in Ca 2+ gradients generated in vitro, which has led to the hypothesis that Ca 2+ gradients in combination with gradients of the monocyte chemoattractant protein (MCP-1) regulate GnRH neuron migration during development Bandyopadhyay et al, 2007).…”
Section: Introductionmentioning
confidence: 99%